Remarks on Germanisms in Polish dialects and related research problems - Kucharzyk, Renata (Papers in Linguistics, 2022)
The article deals with the influence of the German language on Polish dialects and the methodology of etymological studies into dialects. It presents the most important research problems faced by an etymologist dealing with dialectal vocabulary. The most crucial issue is to specify which German dialects are the source of borrowings and whether Germanisms entered the Polish dialects in question directly from German or through another language. Determining the etymology of dialect lexemes is rendered difficult by the lack of adequate sources documenting especially the older dialectal forms. Many Germanisms present in dialects are not attested in written texts, which means that they remain outside the scope of linguistic analysis. Others are sparsely documented, which does not provide precise information about the range of the word, its semantics and phonetics. Moreover, dialects exhibit a tendency towards phonetic transformations of borrowings, which makes these words significantly different from their German sources. The diversity of dialects and the limited range of individual dialects mean that we may deal with borrowings that are some sort of linguistic peculiarities which are difficult to analyse because they have no parallels either in the general language or in other dialects.